Atividades experimentais sobre matéria e energia para o ensino fundamental : abordagem investigativa - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This study portrayed the application of the investigative approach inthe teaching of science, focusing on the thematic axis of matter and energy in the final years ofelementary school, considering the changes introduced by the National Common Curricular Base(BNCC) and the Curriculum Document for Goiás (DC-GO). The main objective was to verify how thepractice of investigative experimental activities contributes to the construction of scientific knowledgeand to the promotion of meaningful learning. To this end, the research was structured in three stages:(1) the systematic review of the literature, which theoretically supported the analysis; (2) theelaboration and application of experimental activities with an investigative approach, organized in adidactic material called “Experimenters in Action”; and (3) the evaluation of the results obtained afterthe application of these activities in a 9th grade class through participant research. The results indicatedthat experimentation, when combined with the investigative approach, favored the articulationbetween theory and practice, stimulated student engagement, and enabled the development offundamental competencies and skills for carrying out small research projects in the school context. Itwas concluded that this methodological approach was effective in engaging students, contextualizingthe scientific content, and bringing it closer to the daily reality of the students.
Experimental activities on matter and energy for elementary education : investigative approach
Keywords: Ensino de Ciências; Abordagem investigativa; Aprendizagem significativa.; Science Teaching; Investigative approach; Meaningful learning; EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS EXATAS E DA TERRA::MATEMATICA